Left ventricular global longitudinal strain predicts mortality and heart failure admissions in African American patients. Issue 5 (8th March 2017) - Kansal, Mayank M.; Mansour, Ibrahim N.; Ismail, Sahar; Bress, Adam; Wu, Grace; Mirza, Omer; Marpadga, Rahul; Gheith, Hana; Kim, Yoonsang; Li, Yien; Cavallari, Larisa; Stamos, Thomas D.
Abstract : Background: Several studies have demonstrated the importance of left ventricular (LV) global longitudinal strain (GLS) as a reliable prognostic indicator in patients with heart failure (HF). These studies have included few African American (AA) patients, despite the growing prevalence and severity of HF in this patient population. Hypothesis: LV GLS predicts long‐term HF admission and all‐cause mortality in AA patients with chronic HF on optimal guideline‐directed medical therapy (GDMT). Methods: We enrolled 207 AA adults, age 56 ± 14.5 years, with New York Heart Association (NYHA) class I through III HF on optimal GDMT from the University of Illinois HF clinic between November 2001 and February 2014. LV GLS was assessed by velocity vector imaging using 2‐, 3‐, and 4‐chamber views. Patients were followed for HF admissions and death for 3 ± 3.0 years. LV GLS value of −7.95 was used as the optimal cutoff point that maximizes sensitivity and specificity Results: LV GLS < −7.95% was significantly associated with higher all‐cause mortality and HF admissions in Kaplan‐Meier survival curves (log‐rank P < 0.001). After incorporation in multivariate Cox proportional hazard models, GLS < −7.95% was found to be an independent predictor of all‐cause mortality (hazard ratio [HR] = 4.04; 95% confidence interval [CI]: 1.07‐15.32; P = 0.04] and HF admissions (HR = 3.86; 95% CI: 1.38‐10.77; P = 0.010). Conclusions: In AA patients with chronic stable HF on GDMT, more impaired LV GLS (< −7.95%) is a strong and independent predictor of long‐term all‐cause mortality and HF admissions.